The Figurative Meaning of Madurese Language: A Semantic Study of Madurese Proverbs - Rifa Efawati; Siti Arifah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This semantic-based research study investigates the figurative language of Madura proverbs. The objectives of this study were to describe the types of figurative language contained in Madura proverbs. Describe the meaning and function of figurative language in Madura proverbs. And also describe the relationship of culture inside Madura proverbs. Research result indicates that in the style of figurative language metaphor based on Haley’s hierarchy in nine metaphors, the metaphors in Madura’s proverbs are energy, terrestrial, cosmos, object, animate, living, and human. Simile in this research includes cosmos, plants, animals, object, and terrestrial. And personifications in this research are animate personification and non-human personification.